32 year follow up of patients following atrial redirection surgery for transposition of the great arteries. (6th September 2019) - Morrison, M. Louise; Grant, Brian; McCrossan, Brian A.; Sands, Andrew J.; Owens, Colum G.; Spence, Mark S.; Casey, Frank A.; Craig, Brian G.; Lockhart, Christopher J.
Abstract: Objective: A significant body of patients who have undergone Mustard or Senning procedure require lifelong follow up. In this retrospective review, we examined the cohort of such patients currently attending our center. Design: Patients who had undergone either Mustard or Senning procedure were identified. We retrospectively reviewed medical records, recorded demographic information and data regarding the clinical state, NHYA class, cardiopulmonary exercise testing, NT‐proBNP measurement, and recent cardiac MRI findings. Results: Forty‐six patients were identified, the mean age was 32.2 years (± 6.1 years), 67.4% were male. Thirty‐two patients (69.6%) had undergone a Senning procedure. The median length of the follow‐up was 32 years. Thirty‐two patients (69.6%) were NHYA class 1. The mean VO2max achieved was 24.2 ± 5.8 mL/min/kg. The mean NT‐proBNP was 266.4 pg/mL (± 259.9 pg/mL). The mean right ventricular end‐diastolic volume (RVEDV) was 212.4 mL ± 73.1 mL (indexed 114.2 mL/m 2 ± 34.4 mL/m 2 ). The mean right ventricular ejection fraction (RVEF) was 53.7% ± 7.9%. The mean left ventricular end‐diastolic volume (LVEDV) was 161.5 mL ± 73.7 mL (indexed 87.8 mL/m 2 ± 41.1 mL/m 2 ). The mean left ventricular ejection fraction (LVEF) was 59.8% ± 5.7%. There was a significant correlation between right ventricular (RV) size on MRI and NT‐proBNP level. Conclusions: We present a relatively well cohort of patients with overall favorable long‐term outcome. The majority of patients are NHYA class 1 and the systemic right ventricular function appears to be well preserved as assessed by MRI. The exercise tolerance is reduced, with the majority of patients achieving around 60% of the estimated VO2max . Regular specialist follow‐up and assessment with advanced imaging at regular intervals remain important for this group.